THE READABILTY OF READING MATERIALS IN ENGLISH TEXTBOOK FOR THE ELEVENTH GRADE STUDENTS OF SMK NEGERI 1 BERINGIN - Theo Kismarianto; Masitowarni Siregar; Yeni Erlita (Universitas Negeri Medan, 2018)
This study focused on the readability of reading materials in English textbook for grade XI students of SMK Negeri 1 Beringin. This study attempted to find out the English reading materials appropriateness in terms of the readability level for the target students. This study was categorized as descriptive quantitative research. The source of the data were the reading materials from English in Professional Job Situations textbook published by Grafindo Media Pratama which was designed under guidance of Kurikulum Tingkat Satuan Pendisdikan (KTSP). The Dale and Chall original formula was used to analyze the data from the textbook. The findings of the study showed that most of the reading materials in English in Professional Job Situations textbook were only appropriate for the 13-15th grade (college) and were considered too hard for the eleventh grade students.Keywords: Readability, The Dale and Chall Original Formula, Readability Formula, English Textbooks for Eleventh Grade Students.